2017
DOI: 10.22373/je.v3i2.3093
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Persepsi Masyarakat Terhadap Kecemasan Kaum Homoseksual/Lesbian

Abstract: Indonesia is the country which does uphold norms and values of its people. Homosexual/Lesbian for most of eartern people is declared as not common sexual orientation. Negative stigma from people caused social anxious for homosexual community. For minority anxiouses show up all togather with attact or negative perpective from society, the strict eastern culture with binding social norms, will give social punishment to individual deviant behaviour such as homosexialbehaviour through humiliation to isolation. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Studies in other countries have also revealed discord in SGM relationships. [49][50][51] In managing the conflicts, it was found that SGM engaged in risky behaviours such as reckless driving, smoking, and substance use as reported by Salvatore and Daftary-Kapur. 52 This is consistent with a finding by Ahmad et al that lesbian adolescents used avoidance coping strategies compared to heterosexual female adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in other countries have also revealed discord in SGM relationships. [49][50][51] In managing the conflicts, it was found that SGM engaged in risky behaviours such as reckless driving, smoking, and substance use as reported by Salvatore and Daftary-Kapur. 52 This is consistent with a finding by Ahmad et al that lesbian adolescents used avoidance coping strategies compared to heterosexual female adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Ditambah lagi dengan keadaan di masyarakat bahwa adanya pandangan yaitu pandangan masyarakat terhadap fenomena lesbian sangat berkaitan dengan latar belakang pendidikan, budaya, lingkungan, dan agama (Jalil, 2017). Dimana homoseks dan lesbian dalam kehidupan masyarakat khususnya di negara Indonesia, tidak sesuai dengan struktur, nilai, norma dan sistem sosial masyarakat Indonesia, dengan demikian mereka disebut sebagai golongan orang-orang yang telah melanggar aturan agama dan adat istiadat serta norma hukum yang berlaku di Indonesia (Bulantika, 2017).…”
Section: Pendahuluanunclassified
“…Homosexuals comprise two groups, lesbian and gay. Although in some references, the term homosexual is more used for men who suffer from irregularities, while for women, I know it as lesbian [17,18]. As with homosexuals, it defines transgender as a condition or condition where there is a gap between a person's physical and psychological state, when someone feels that his physical condition is not under what they felt, with sexual identity [19,20].…”
Section: Introductionmentioning
confidence: 99%